How Glucosinolates Affect Generalist Lepidopteran Larvae: Growth, Development and Glucosinolate Metabolism - Jeschke, Verena; Kearney, Emily E.; Schramm, Katharina; Kunert, Grit; Shekhov, Anton; Gershenzon, Jonathan; Vassão, Daniel G. (Frontiers in Plant Science, 2017)
Multiple lepidopteran larvae feed successfully on plants containing glucosinolates despite the diverse array of toxic and deterrent breakdown products, such as isothiocyanates (ITCs), formed upon plant damage. While much is known about how specialist lepidopterans metabolize and tolerate glucosinolates, there is little information about the metabolic fate of these plant defense compounds in specialized herbivores. Employing 13C- and 14C-labeled 4-methylsulfinylbutyl glucosinolate (glucoraphanin), we identified and quantified the major detoxification products of glucosinolates and ITCs in selected specialized and generalist larvae. While specialists prevented glucosinolate hydrolysis or diverted hydrolysis to form nitriles, hydrolysis in generalists proceeded to toxic ITCs, of which a portion were conjugated to glutathione. However, a large amount of ITCs remained unmodified, which may have led to the observed negative effects on growth and development. The performance of two generalist-feeding caterpillars, Spodoptera littoralis (African cotton leafworm) and Mamestra brassicae (cabbage moth) on Arabidopsis thaliana Col-0 and various glucosinolate-deficient mutants was investigated from hatching until pupation. We found that glucosinolates negatively affected larval growth and development, but not survival, with aliphatic glucosinolates having stronger effects than indolic glucosinolates, and the combination of the two glucosinolate types being even more detrimental to growth and development. Curiously, last instar larvae grew better on wild type than on non-glucosinolate-containing plant lines, but this could not be attributed to a change in detoxification rate or feeding behavior. Glucosinolates thus appear to be effective defenses against generalist lepidopteran herbivores at least during most stages of larval development. Nevertheless, the reversal of negative effects in the oldest instar is intriguing, and further investigation of this phenomenon may shed light on how generalists adjust their physiology to feed on diets with many different types of plant defense compounds.